Topeng Cirebon Dalam Teori Fungsionalisme - Toto Sudarto (Institut Seni Indonesia Surakarta, 2013)
The word ‘function’ has been elaborated in many aspects. In every single context it also has a different meaning. Despite having a specific meaning, the meaning of the word ‘function’ differs from one discipline to another. A.R. Redcliffe Brown and Bronislow K. Malinowski are the pioneers of the theory of function amongst anthropologists. Their assumption, which is based on their theoretical constructs related to social and cultural integration, has an independent system and consists of every single part or element, since every element or part is not autonomous but rather is connected to and even dependent on each other. On the other hand, every element or part of the system can exist because it is needed, or experiences an interdependency or inherence not by accident, and its whole appearance belongs entirely to the orientation of a living system. The changing of each element will have an impact on other elements. The Cirebonese masked dance can be studied from several disciplines. In this article, the Cirebonese masked dance is examined using a theory of function, especially functionalism of anthropology. In addition the dance is assumed to be a system of performance which consists of various elements that are related to each other. This article on the Cirebonese masked dance will explore its dance symbols through the mask, in relation to its religious, educational, socio-political, economic, bureaucratic, and aesthetical elements.Keywords : function, theory of function, Cirebonese masked dance, functionalism.